Molecular recognition by multiple metal coordination inside wavy-stacked macrocycles - Takashi Nakamura (Nature Portfolio, 2017)
Synergistic use of coordination bonds that are strong and reversible realizes unique molecular recognition in artificial systems. Here, the authors show that a zinc-based metallomacrocyle can bind dicarboxylic acids of suitable length at specific metal sites by shape deformation and dimerization.